Sulfur and nitrogen mustards induce characteristic poly(ADP-ribosyl)ation responses in HaCaT keratinocytes with distinctive cellular consequences. (26th February 2016) - Mangerich, Aswin; Debiak, Malgorzata; Birtel, Matthias; Ponath, Viviane; Balszuweit, Frank; Lex, Kirsten; Martello, Rita; Burckhardt-Boer, Waltraud; Strobelt, Romano; Siegert, Markus; Thiermann, Horst; Steinritz, Dirk; et al.
Graphical abstract: Highlights: Detailed analysis of sulfur and nitrogen mustard-induced PARylation in HaCaT cells PARylation participates in mustard-induced stress response in a substance-specific manner PARP inhibitors potentiate CEES-induced genome instability With limitations, CEES and HN2 can be used as surrogates to study SM-related toxicity PARP inhibitors should be considered with caution as SM antidotes, due to potential long-term effects Abstract: Mustard agents are potent DNA alkylating agents with mutagenic, cytotoxic and vesicant properties. They include bi-functional agents, such as sulfur mustard (SM) or nitrogen mustard (mustine, HN2), as well as mono-functional agents, such as "half mustard" (CEES). Whereas SM has been used as a chemical warfare agent, several nitrogen mustard derivatives, such as chlorambucil and cyclophosphamide, are being used as established chemotherapeutics. Upon induction of specific forms of genotoxic stimuli, several poly(ADP-ribose) polymerases (PARPs) synthesize the nucleic acid-like biopolymer poly(ADP-ribose) (PAR) by using NAD + as a substrate. Previously, it was shown that SM triggers cellular poly(ADP-ribosyl) ation (PARylation), but so far this phenomenon is poorly characterized. In view of the protective effects of PARP inhibitors, the latter have been proposed as a treatment option of SM-exposed victims. In an accompanying article (Debiak et al., 2016 ), we have provided an optimized protocol for the analysis of the CEES-induced PARylation response in HaCaT keratinocytes, which forms an experimental basis to further analyze mustard-induced PARylation and its functional consequences, in general. Thus, in the present study, we performed a comprehensive characterization of the PARylation response in HaCaT cells after treatment with four different mustard agents, i.e., SM, CEES, HN2, and chlorambucil, on a qualitative, quantitative and functional level. In particular, we recorded substance-specific as well as dose- and time-dependent PARylation responses using independent bioanalytical methods based on single-cell immuno-fluorescence microscopy and quantitative isotope dilution mass spectrometry. Furthermore, we analyzed if and how PARylation contributes to mustard-induced toxicity by treating HaCaT cells with CEES, SM, and HN2 in combination with the clinically relevant PARP inhibitor ABT888. As evaluated by a novel immunofluorescence-based protocol for the detection of N7-ETE-guanine DNA adducts, the excision rate of CEES-induced DNA adducts was not affected by PARP inhibition. Furthermore, while CEES induced moderate changes in cellular NAD + levels, annexin V/PI flow cytometry analysis revealed that these changes did not affect CEES-induced short-term cytotoxicity 24 h after treatment. In contrast, PARP inhibition impaired cell proliferation and clonogenic survival, and potentiated micronuclei formation of HaCaT cells upon CEES treatment. Similarly, PARP inhibition affected clonogenic survival of cells treated with bi-functional mustards such as SM and HN2. In conclusion, we demonstrate that PARylation plays a functional role in mustard-induced cellular stress response with substance-specific differences. Since PARP inhibitors exhibit therapeutic potential to treat SM-related pathologies and to sensitize cancer cells for mustard-based chemotherapy, potential long-term effects of PARP inhibition on genomic stability and carcinogenesis should be carefully considered when pursuing such a strategy.